Etiology and Pathogenesis of Macrocytic Anemia - I Komang Gede Andhika (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Anemia is the most common conditions detected by primary care doctors in Indonesia and worldwide. In 2010, the global prevalence of anemia was 32.9%; that is, more than 2.2 billion people have anemia in the world. Macrocytic anemia refers to a condition that refers to macrocytosis, or when the mean corpuscular volume (MCV) is greater than 100 fL in moderate anemia, the hemoglobin is less than 12 g/dL, or the hematocrit is less than 36%. To identify the etiology and course of the disease in macrocytic anemia. This writing uses the method of studying the relevant literature related to the etiology and course of the disease, macrocytic anemia. The search engines used in this paper include Pubmed, Google Scholar, Research Gate, NCBI, and BMC. This article uses 22 articles that were used as references in its preparation. Megaloblastic anemia has etiologies in the form of vitamin B12 and folate deficiency, while non-megaloblastic anemia has etiologies such as alcohol consumption, MDS, hyperthyroidism, etc. The disease course of the two types of macrocytic anemia also differs based on the type, namely megaloblastic and non-megaloblastic. In general, macrocytic anemia is divided into megaloblastic anemia and non-megaloblastic anemia; these divisions have different etiologies dan pathogenesis.